The 2008 Cholera Epidemic in Zimbabwe: Experience of the icddr,b Team in the Field (Journal of Health, Population and Nutrition, 2011)
During August 2008–June 2009, an estimated 95,531 suspected cases of cholera and 4,282 deaths due to cholera were reported during the 2008 cholera outbreak in Zimbabwe. Despite the efforts by local and international organizations supported by the Zimbabwean Ministry of Health and Child Welfare in the establishment of cholera treatment centres throughout the country, the case-fatality rate (CFR) was much higher than expected. Over two-thirds of the deaths occurred in areas without access to treatment facilities, with the highest CFRs (>5%) reported from Masvingo, Manicaland, Mashonaland West, Mashonaland East, Midland, and Matabeleland North provinces. Some factors attributing to this high CFR included inappropriate cholera case management with inadequate use of oral rehydration therapy, inappropriate use of antibiotics, and a shortage of experienced healthcare professionals. The breakdown of both potable water and sanitation systems and the widespread contamination of available drinking-water sources were also considered responsible for the rapid and widespread distribution of the epidemic throughout the country. Training of healthcare professionals on appropriate cholera case management and implementation of recommended strategies to reduce the environmental contamination of drinking-water sources could have contributed to the progressive reduction in number of cases and deaths as observed at the end of February 2009. Key words: Cholera; Disease outbreaks; Drug therapy; Mortality; Oral rehydration therapy; Zimbabwe DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8909 JHPN 2011; 29(5): 541-546